2021
DOI: 10.1088/1367-2630/ac0755
|View full text |Cite
|
Sign up to set email alerts
|

Practically secure quantum position verification

Abstract: We discuss quantum position verification (QPV) protocols in which the verifiers create and send single-qubit states to the prover. QPV protocols using single-qubit states are known to be insecure against adversaries that share a small number of entangled qubits. We introduce QPV protocols that are practically secure: they only require single-qubit states from each of the verifiers, yet their security is broken if the adversaries sharing an impractically large number of entangled qubits employ teleportation-bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This work has been used to build an authenticity, integrity, and replay protection scheme for quantum messages by Barbeau et al, 14,15 with demonstrated soundness and completeness, and to analyze attack probability. Other quantum data authentication efforts include the work of Das and Siopsis, 16 building on a position authentication protocol, and Satoh et al, 17 building on the concept of quantum state tomography.…”
Section: Related Workmentioning
confidence: 99%
“…This work has been used to build an authenticity, integrity, and replay protection scheme for quantum messages by Barbeau et al, 14,15 with demonstrated soundness and completeness, and to analyze attack probability. Other quantum data authentication efforts include the work of Das and Siopsis, 16 building on a position authentication protocol, and Satoh et al, 17 building on the concept of quantum state tomography.…”
Section: Related Workmentioning
confidence: 99%